1991
DOI: 10.1021/bi00107a023
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of protein 4.1 binding to inside-out membrane vesicles by phosphorylation

Abstract: The effect of phosphorylation on the binding of protein 4.1 to erythrocyte inside-out vesicles was investigated. Protein 4.1 was phosphorylated with casein kinase A, protein kinase C, and cAMP-dependent protein kinase. An analysis of the phosphopeptides generated by alpha-chymotryptic and tryptic digestion indicates these kinases phosphorylate similar as well as distinct domains within protein 4.1. All three enzymes catalyze the phosphorylation to varying degrees of the 46-, 16-, and 8-10-kDa fragments derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This is consistent with the fact that it directly interacts with aPKC (Fig. 1 D) and with previous studies showing that the FA domain of other FERM family members acts as an important phosphorylation-dependent regulatory element (Danilov et al, 1990; Chao and Tao, 1991; Manno et al, 2005; Baines, 2006; Nakajima and Tanoue, 2011). Therefore, we focused our analysis on the FA domain of Yrt, which contains 12 serine/threonine (S/T) residues (Fig.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the fact that it directly interacts with aPKC (Fig. 1 D) and with previous studies showing that the FA domain of other FERM family members acts as an important phosphorylation-dependent regulatory element (Danilov et al, 1990; Chao and Tao, 1991; Manno et al, 2005; Baines, 2006; Nakajima and Tanoue, 2011). Therefore, we focused our analysis on the FA domain of Yrt, which contains 12 serine/threonine (S/T) residues (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Several observations based on studies in vitro strongly suggest that phosphorylation may modify interactions between proteins, leading in all cases to a reduced affinity. [9][10][11][12][13][14][15][16][17][18] Our study shows an ellipto-poikilocytosis, an abnormal spectrin dimer percentage and an increased ␤-spectrin phosphorylation in 10 patients with leukemia at diagnosis with their normalization during the remission phase. Although in vitro studies showed that the phosphorylation did not affect the dimer-tetramer equilibrium of spectrin 41,42 and the erythrocyte shape, 43 our results show a different pattern in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…8 Evidence shows that the shape and the deformability of the red blood cell membrane are very sensitive to the state of phosphorylation. [9][10][11][12][13][14][15][16][17][18] In particular, increased phosphorylation of ␤-spectrin decreases membrane mechanical stability. 19 Several acquired abnormalities of erythrocytes and platelets have been described in leukemia and myelodysplastic syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of observations in the literature, stemming primarily from studies on purified membrane components, have suggested that the glycophorin C-protein 4.1 bridge to the membrane skeleton might be physiologically regulated (22,24,(32)(33)(34). However, except for the impact of protein kinase C phosphorylation on this bridging function (35), none of the potential regulatory pathways has been validated in intact erythrocytes.…”
Section: Resultsmentioning
confidence: 99%